The Effects of Combined Verbal Encouragement and Technical Instruction on Technical Skills and Psychophysiological Responses During Small-Sided Handball Games Exercise in Physical Education - Sahli, Feten; Hammami, Raouf; Sahli, Hajer; Jebabli, Nidhal; Selmi, Walid; Zghibi, Makrem; Tillaar, Roland van den (Frontiers in Psychology, 2022)
To examine the effects of combined positive verbal encouragement and general technical guidelines on technical and psychophysiological parameters in pupils during a small-sided handball passing game. Twenty secondary school pupils (age, 16 ± 1 years; body mass, 55.3 ± 6.6 kg; body height, 1.77 ± 0.13 m; BMI, 22.6 ± 2.2 kg.m-1) performed small-sided games (2x10 min) with three conditions: small-sided game 1) with combined verbal encouragement and technical instruction; 2) with technical instruction; 3) without any instruction (control) in which the passes for each pupil in each set was measured together with the rate of perceived exertion (RPE) and feeling mood after the first and second set. Results: A two-way analysis of variance demonstrated that the combined condition resulted in more passes compared to the technical instruction and control conditions, while the number of passes increased in set 2 for all conditions. RPE and the feeling mood were also differently between the conditions. Combined verbal encouragement and technical instruction during handball exercise were more beneficial for optimal passing numbers, positive mood with less perception of physical effort compared to only technical instruction and a control condition. The results evidenced positive acute effects of combined verbal encouragement and technical instruction during handball, indicating the usefulness of these training method for optimal passing numbers, positive mood with less perception of physical effort in physical education pupils. Future studies should evaluate the applicability combined verbal encouragement and technical skills in the training of other conditioning capacities and the individual responsiveness of players toward verbal encouragement tasks.